Phosphorus uptake, transport, and signaling in woody and model plants - Xingyan Fang; Deming Yang; Lichuan Deng; Yaxin Zhang; Zhiyong Lin; Jingjing Zhou; Zhichang Chen; Xiangqing Ma; Meina Guo; Zhaohua Lu; Liuyin Ma (Forestry Research)
Phosphorus (P), a critical macronutrient for plant growth and reproduction, is primarily acquired and translocated in the form of inorganic phosphate (Pi) by roots. Pi deficiency is widespread in many natural ecosystems, including forest plantations, due to its slow movement and easy fixation in soils. Plants have evolved complex and delicate regulation mechanisms on molecular and physiological levels to cope with Pi deficiency. Over the past two decades, extensive research has been performed to decipher the underlying molecular mechanisms that regulate the Pi starvation responses (PSR) in plants. This review highlights the prospects of Pi uptake, transport, and signaling in woody plants based on the backbone of model and crop plants. In addition, this review also highlights the interactions between phosphorus and other mineral nutrients such as Nitrogen (N) and Iron (Fe). Finally, this review discusses the challenges and potential future directions of Pi research in woody plants, including characterizing the woody-specific regulatory mechanisms of Pi signaling and evaluating the regulatory roles of Pi on woody-specific traits such as wood formation and ultimately generating high Phosphorus Use Efficiency (PUE) woody plants.